Revisiting the use of ChatGPT in Business and Educational Fields: Possibilities and Challenges - Sk Rezwan Shihab; Nahida Sultana; Abdul Samad (CV. Multi Kreasi Media, 2023)
ChatGPT is the commonly known platform of modern natural language processing technology, developed by OpenAI. It is based on the GPT-3.5 architecture, an extension of the GPT-3 model that has undergone additional performance and efficiency optimization. The model is made to interpret inputs in natural language and provide human-like answers. A sizable amount of text data from numerous sources, including books, journals, and websites, was used to train it. To train the model to recognize the patterns and structure of natural language, unsupervised learning approaches are used. Overall, ChatGPT is a major advance in natural language processing and has the potential to completely change how we communicate with machines. It's conceivable that ChatGPT will be used in more sophisticated ways across a range of industries, from education to entertainment and beyond, as technology advances. ChatGPT has been utilized for research in addition to its potential uses in many fields. The concept has been used by researchers to investigate the social and cultural implications of language use as well as the patterns and structures of natural language. ChatGPT does have some restrictions, despite its many uses. Understanding the nuances and intricacies of human languages, such as sarcasm, irony, and humor, is one of the hardest hurdles in natural language processing. Due to ChatGPT's limited capacity to comprehend and produce responses that reflect these subtleties, it occasionally produces unsuitable or irrelevant responses. The amount of computing required by ChatGPT presents another difficulty. The model needs a lot of processing power to run, which can make it challenging to implement in environments with few resources. Researchers are investigating novel methods and approaches to natural language processing to address these issues, including creating new models that can better comprehend the subtleties of human language and enhancing the effectiveness of current models. In general, ChatGPT is a significant advancement in natural language processing and has the potential to change how we communicate with machines. In the years to come, it's possible that ChatGPT and other natural language processing models will be used in ever more sophisticated ways as technology develops and improves. .